Digital marketing's impact on consumer trust and purchasing decisions for makeover cosmetics on shopee - Kusnandar, Acu (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
With the increasing complexity of business today, competition in the e-commerce sector is becoming increasingly fierce. One major challenge faced by businesses is declining sales trends and difficulties in building consumer trust on e-commerce platforms. To address this, companies leverage digital marketing strategies, including Shopee Live, to expand their marketing reach and strengthen consumer engagement. This study aims to analyze the effect of digital marketing on consumer trust and purchasing decisions. Conducted in Bandung, Indonesia, the research employed a quantitative approach involving 170 respondents aged 17 to over 35 years, selected using purposive sampling. Data were collected through structured questionnaires using a Likert scale (1-5) and analyzed using multiple linear regression with SPSS version 17.0. The results reveal a significant positive effect of digital marketing on consumer trust, with a coefficient value of 0.295, as well as a significant positive effect on purchasing decisions, with a coefficient value of 0.226. These findings indicate that Shopee Live as a digital marketing tool plays a critical role in enhancing consumer trust and influencing purchasing decisions. The results can be utilized to develop more targeted digital marketing strategies and improve platform performance, ultimately driving better consumer engagement and sales growth.